Penyusunan Stratigi Pengembangan Industri Penyamakan Kulit di yogyakarta - Purwaningsih, Isti (Jurnal Teknologi Pertanian, 2003)
This research was focused on development of strategic formation for tennage manufacture in Yogyakarta. Based on Primary and secondary data, factors of strength, weakness, opportunity, and threat were determined. From these factors, strategy matrices was arranged which gave four alternative strategy. They are SO strategy (strength-opportunity), WO strategy (weakness-opportunity), ST strategy (strength-threat), and WT strategy (weakness-threat). To obtain strategy priority, assessment using AHP method (Analytical Hierarchy Process) was carried out. From assessment using AHP method showed that Production and Technology Development strategy was the first priority. The second and third priority was Increasing Quality and Quantity of Raw Material, and Human Resources Development. Market Development and Supporting industry Development were the fourth and fifth priority in tennage industries development.Â  Each group of strategy consists of several development alternative strategies. Â  Keyword: development strategic, tennage manufacture, SWOT analysis, and AHP method